Long-term treatment of antipsychotics and combined therapy with other psychotropic medications inducing weight gain in patients with non-affective psychotic disorder: Evidence from GROUP, a longitudinal study. (August 2022) - Burin, Luisa M.; Hahn, Margaret K.; da Rocha, Neusa S.; van Amelsvoort, Therese; Bartels-Velthuis, Agna A.; Bruggeman, Richard; de Haan, Lieuwe; Schirmbeck, Frederike; Simons, Claudia J.P.; van Os, Jim; Cahn, Wiepke
Highlights: Individuals using only antipsychotics gain weight during long-term treatment. Individuals using antipsychotics and other psychotropics also gain weight. Continuous long-term weight gain may be primarily driven by antipsychotics. Abstract: Introduction: Antipsychotics (APs) can cause weight gain. Little is known about changes in weight when APs are combined with other psychotropics. This study examines the weight change in patients undergoing long-term treatment with APs or with AP combined with other psychotropics. Methods: Patients with non-affective psychotic disorder from the GROUP study were divided into three groups: AP medication group (APm) ( n  = 100), AP in combination with other psychotropics (APc) ( n =  73), and medication-free (Meds-free) ( n =  100). Weight change was examined at inclusion and after three years using a paired-sample t-test. An Independent-sample t-test was performed to evaluate weight change among patients taking clozapine, olanzapine, and quetiapine and individuals not taking these medications. Linear regression was performed to evaluate the association between covariates and weight. Results: Patients in the APm group [mea n =  1.800 kg, t(99)=2.849, 95% CI(0.546, 3.054), p  = 0.005] and the APc group [mea n =  1.877 kg, t(72)=2.688, 95% CI(0.485, 3.268), p =  0.009] showed significant weight gain. Patients taking clozapine, olanzapine or quetiapine showed significant weight gain compared to those not taking these medications [mean difference=1.707 kg, t(271)= 2.061, 95% CI(0.077, 3.337), p =  0.040)]. Conclusion: Patients receiving APs and APs with other psychotropics gain weight during long-term treatment. It is possible that weight gain is mainly driven by APs.